Tools and models for distance teaching in an English Language and Culture university course: the flipped classroom and cooperative learning in a digital environment (Altre Modernità, 2022)
The Covid-19 pandemic emergency has contributed to shift towards a more learner-centred teaching approach accelerating an ongoing trend in the university system. Re-arranging teaching materials and devices in different forms using digital tools and delivering online lessons, has been a complex challenge for academics. This necessity to re-adapt and possibly implement and re-shape traditional contents has contributed to consolidate teaching strategies as the flipped classroom (integration of pre-recorded lectures with online synchronous lessons) cooperative learning among peers (both in class and on online platforms with discussion groups), and small group teaching. These teaching strategies have also brought about a general re-thinking of learning strategies on the students’ part. To meet students’ needs in this emergency situation, materials have also been frequently developed by teachers themselves. Given such premises, this paper reports on the challenging attempt to adopt the afore-mentioned teaching strategies in an online course (English Language and Culture) held in 2020/21 at the Department of Education Science (Roma Tre University), also providing the students’ response to a questionnaire submitted after the completion of the course.